A study of efficacy and safety of high‐intensity focused ultrasound for the treatment of melasma in Asians: A single‐blinded, randomized, split‐face, pilot study. (7th June 2019) - Vachiramon, Vasanop; Iamsumang, Wimolsiri; Chanasumon, Nongsak; Thadanipon, Kunlawat; Triyangkulsri, Korn
Abstract: Background: A recent report suggested potential of high‐intensity focused ultrasound in improving UVB‐induced hyperpigmentation in patients with Fitzpatrick skin type IV, but reports regarding its efficacy in other hyperpigmented conditions including melasma are lacking. Objectives: To investigate efficacy and safety of high‐intensity focused ultrasound for the treatment of melasma in Asians. Methods: Each side of the face of 25 melasma patients was randomized to receive 3‐monthly sessions of high‐intensity focused ultrasound treatment or serve as control. Lightness index, Melasma Area and Severity Index of malar area (MASIm ) by blinded dermatologists, self‐evaluated improvement and satisfaction scales by patients, and side effects were assessed every 4 weeks for 20 weeks. Results: Twenty‐one patients with Fitzpatrick skin type III and IV completed the study. There was a greater reduction of relative lightness index and MASIm after treatment in high‐intensity focused ultrasound‐treated side. However, there were no statistically significant differences between both sides. More than 50% improvement on treatment side was rated in 11 patients (52.4%). Side effects were minimal. None had worsening of melasma. Conclusions: High‐intensity focused ultrasound may be an adjuvant for treatment of melasma. Further studies with larger sample size and proper parameter settings are recommended to determine its efficacy.